THE INFLUENCE OF CORPORATE SOCİAL RESPONSİBİLİTY, FİRM CHARACTERİSTİCS, AND GOOD CORPORATE GOVERNANCE ON EARNİNGS MANAGEMENT - Mardianto Mardianto; Selvina Selvina (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
This paper aims to examine the factors that have impact on earnings management of listed company in Indonesia. The independent variables considered in this study are corporate social responsibility, firm characteristics such as leverage, firm size, and financial performance. Good corporate governance mechanisms such as board of commissioners size, audit committee size, and managerial ownership are also part of this study. The finding of this study is financial performance has significant and positive impact on earnings management and board of committee size has a significant and negative impact on earnings management. The other independent variables is insignificantly affect earnings management. These results were achieved from the data of 44 companies for a period of five years from 2016 to 2020 using purposive sampling and were analyzed using panel regression techniques supported by SPSS and E-Views.